Characteristics of Cold Start Behavior of PEM Fuel Cell with Metal Foam as Cathode Flow Field under Subfreezing Temperature. Issue 11 (2nd September 2021) - Huo, Sen; Li, Lincai; Shi, Weiyu; Wang, Renfang; Lu, Bingbing; Yin, Yan; Zhu, Chaoyi; Wang, Yang; Jiao, Kui; Hou, Zhongjun
ABSTRACT: Cold start has been realized as an important issue for PEMFC in its global commercialization. As is well-known, the conventional "channel-rib" type flow field will surely lead to several problems, such as water accumulation under the rib, resulting in slow water removal and serious ice blockage in the pores. In recent years, with the fast development of metal foam materials, metal foam has been recognized as a promising alternative replacement of the conventional "channel-rib" type flow field. In this study, a cold start model of PEMFC is established under sub-zero temperature. The coupled transport processes of heat, mass and charge in PEMFC under various subzero temperatures and startup modes are simulated. The results show that ice formation is slower in the PEMFC with metal foam as cathode flow field in cold start process, due to the superior performance of metal foam in water removal and uniform distribution of gas supply. However, the excellent thermal conductivity of metal foam could also result in faster heat loss from PEMFC. Furthermore, ice formation is highly dependent on the supercooled water transfer behavior, though small amount of supercooled water is maintained in the cell. This work aims to provide a systematic analysis for the cold start behavior of PEMFC with metal foam flow field.